Cinema by the lenses of Edgar Morin's theories of complexity:: a productive reflection for the present days - Kahtalian, Marcos (2020)
The purpose of this article is to highlight the productive relationships between Edgar Morin's (1996) theories of complexity and cinema, understood from this frame as a complex art, foreshadowing his later thinking. We work with the hypothesis that the understanding of cinema as a complex art may be relevant to the recent discussion on the different modalities of viewing the film, with the perceived decline of movie theaters as a point of reception for the film. To this be done, not only contributions from theorists of complexity and cultural networks will be mobilized, but also specific contributions from theories of cinematographic form and cinema as a social practice, also from Morin (2014) and the most recent discussion on ontology of cinema, as can be seen in Jacques Aumont (2012), among other authors.